Risk-Based Monitoring: Implications of the US FDA Guidance for Pharmaceutical Physicians - Stoltz, Randall R. (Pharmaceutical medicine, 2013)
The Food and Drug Administration (FDA) released a Guidance for Industry on “Oversight of Clinical Investigations: A Risk-Based Approach to Clinical Monitoring” in August 2013. In summary, the guidance says that effective monitoring is critical to human subject protection and the conduct of high quality studies and that sponsors are responsible for ensuring proper oversight of the investigation, but it does not specifically state how sponsors should do the monitoring. The guidance discusses on-site as well as centralized monitoring; however, it is intended to inform industry of FDA’s support of alternative approaches. There is more focus on critical study parameters including areas such as: endpoints, serious adverse events, randomization/blinding, consent, and eligibility criteria. The guidance points out that “The most important tool for ensuring human subject protection and high-quality data is a well-designed and articulated protocol.” In addition, the types and frequency of monitoring will depend on factors such as: complexity of the study design, types of endpoints, types of subjects, investigator/site experience, relative safety of the product, quantity of data, and the stage of study. Risk-based monitoring is now becoming a reality and sponsors and contract research organizations (CROs) are beginning to experiment with this option. Sites and sponsors will have to develop better metrics to track various functions that can differentiate specific data points that may require more or less verification. Raising the bar for quality at investigator sites will be needed and advanced training/certification of key staff members, as well as site certification, may play an even bigger role. This will likely separate better sites from ones that are new to industry or need closer oversight. Sponsors and sites will need to keep in mind the end result should be protecting human subjects in clinical trials. Finding the best as well as cost effective methods will be the challenge.